READING ECOLOGICAL IMAGINATION IN ARABIC RELIGIOUS LITERATURE OF WEST JAVANESE PESANTREN: AN ECOTHEOLOGICAL STUDY OF NATURAL AESTHETICS AND ISLAMIC VALUE TRANSMISSION - Silviana Zahra; Syarifah Syarifah; Rizqa Amelia; Ekarina Katmas; Akhmad Nizar (Jurnal Lektur Keagamaan, 2026)
This article examines ecological imagination in Arabic religious literature taught in West Javanese pesantren. While pesantren have long been recognized as central institutions for the transmission of Islamic knowledge, moral formation, and the preservation of kitab kuning traditions, the ecological meanings embedded in Arabic literary and religious texts remain underexplored. Existing studies tend to separate the study of pesantren textual traditions from the study of eco-pesantren practices, leaving insufficient attention to how Arabic religious literature may function as a source of ecological awareness. Using a qualitative textual-cultural approach, this study combines ecocriticism, Islamic ecotheology, content analysis, and limited ethnographic observation. The primary textual data include selected fragments from Qaṣīdat al-Burdah, Ta‘līm al-Muta‘allim Ṭarīq al-Ta‘allum, al-Ḥikam al-‘Aṭā’iyyah, and Dīwān al-Imām al-Shāfi‘ī, while contextual data are drawn from selected pesantren traditions in West Java, including Cipasung, Buntet, Ath Thaariq, and the Ekopesantren movement. The findings show that Arabic religious literature in pesantren contains a latent ecological archive. Natural images such as water, rain, light, earth, trees, valleys, and cosmic order function not only as rhetorical ornaments, but also as signs of divine mercy, beauty, balance, and moral responsibility. However, these ecological meanings often remain implicit because pesantren pedagogy tends to emphasize linguistic mastery, rhetorical appreciation, memorization, and general moral instruction. This study argues that ecotheological hermeneutics can reveal the ecological potential of Arabic religious texts while connecting classical Arabic imagery with the local ecological experiences of West Javanese santri. The article contributes to the study of Nusantara religious literature by showing that pesantren-based Arabic literature can serve as a bridge between textual tradition, Islamic environmental ethics, and contemporary ecological consciousness.